How to Improve Process Effectiveness in a Service Company? Restaurant Case Study - Monika KOSACKA-OLEJNIK (Communications of International Proceedings, 2021)
Service sector contributes a high proportion of GDP worldwide. It is important to enable service companies to improve their performance. Thus, the purpose of this paper is to present the method used for process effectiveness assessment in a service company. The literature reports on applications of lean management in service businesses, and while food services belong in this category, the literature contains few works on specific applications in this domain but there is missing a concept useful for process effectiveness assessment. In this study the methodology is presented and verified in polish restaurant with a significant improvement in process effectiveness. The results indicate that methodology may be used in restaurants and other services, too. Future researchers may test this methodology for other service sectors and country. This is the first paper empirically validating the lean service effectiveness assessment. The findings of the paper will be of value to lean service practitioners.
Keywords: Food service; process effectiveness; restaurant; lean management